KARAKTERISTIK TENAGA KERJA PELAKU MOBILITAS SIRKULER DI KECAMATAN KALAWAT KABUPATEN MINAHASA UTARA - Astrid ., Salama; Theodora M. Katindagho; Benu Olfie L.S (Sam Ratulangi University, 2017)
This research aims to study the characteristics of circular mobility labor actors in Sub-district of Kalawat and what the encouraging and binding factors that affect labor circular mobility. The data used in this study are primary data and secondary data. The variables used in this study is the characteristics of respondents, the reason for doing the circular mobility, factors that encourage circular mobility, and the binding factor in the area of origin. Data analysis techniques in this research is descriptive and data presented in table format.The results of this study indicate that there is a dominant factor driving of labor force in the Sub-district of Kalawat to do circular mobility such as: education, transportation, and mileage. While the factors that bind labor circular mobility to remain in the Sub-district of Kalawat is the status of home ownership and living expenses.